618 Educational development of paediatric clinicians working in the NHS 111 Paediatric Clinical Assessment Service (PCAS) to optimise the quality of paediatric consultations. (17th August 2022) - Stilwell, Philippa; Wojciechowska, Agnieszka; Turner, Joanne; Thornton, Sam; Wickham, Tracy; Oloughlin, Kate; Supple, David; Kenny, Simon; Owen, Richard; Mitchell, Raziya; Stuttard, Gareth; Maconochie, Ian
Abstract : Aims: A Paediatric Clinical Assessment Service (PCAS) in NHS 111 was established in 2021, hosted by Integrated Care 24 (IC24). The objectives were to: Recruit paediatric clinicians (doctors and Advanced Nurse Practitioners (ANPs)) to manage clinical calls for under 16 year olds within the PCAS; Design and evaluate an induction and training programme to support PCAS clinicians and optimise the quality of paediatric calls taken within this service. Methods: In 2021, a recruitment advertisement via the RCPCH described the opportunity for paediatric clinicians to join the PCAS, with an expression of interest form hosted on an RCPCH webpage. Following completion of on-boarding (human resources checks, contractual arrangements and IT set-up), paediatric clinicians were inducted into the PCAS. An ongoing virtual educational support programme was designed, with feedback collected from clinicians (via MS Forms survey) four months following its establishment. Results: 105 paediatric clinicians (101 doctors and 4 ANPs) expressed an interest through the RCPCH call out, of whom 91 progressed to on-boarding. 27 paediatric clinicians were inducted (virtually) and have worked at least one shift within the PCAS. The clinician survey was responded to by 21 paediatricians (13 ST4-8 trainees or clinical fellows, 7 active Consultants and 1 retired Consultant; response rate 78%). All respondents found the induction 'very useful' (n = 10, 48%) or 'useful' (n = 11, 52%) Reverse shadowing (in the live environment) and video examples of calls were reported by respondents as ideas that could have further improved the induction experience. 5 paediatricians (24%) reported enjoying the PCAS work 'somewhat' with the remaining 16 (76%) enjoying it 'very much'. 20 (95%) reported feeling 'very well supported' during work and 21 (100%) reported that the PCAS adds value to NHS 111 services. In particular, 5 case types were highlighted by respondents as those in which they felt they could best add value to the service; the unwell infant, fever, rashes, respiratory illness and head injury. 8 of 9 (89%) who had attended the educational (clinical forum) meetings reported finding them 'useful' or 'very useful'. 5 of 9 (55%) noted that they would be happy for non-paediatric clinicians to also join the foru9 respondents were interested in supervising trainees within the PCAS, and 4 in being supervised (i.e. to gain further feedback about their communication, remote assessment skills, decision making and use of the directory of services). All clinicians working in the PCAS have had their consultations audited against the Royal College of General Practice (RCGP) toolkit, with the average audit outcome score = 98.5%. Conclusion: Most paediatric clinicians like working within the NHS111 PCAS and think it adds value to NHS111 CAS services. The clinical forums are a useful means to enable professional peer learning and reflection on clinical case encounters. Future work will establish PCAS supervision sessions, to facilitate immediate feedback and completion of (e-portfolio) workplace based assessments for trainees, using the recently published paediatric NHS 111 consultation framework, learning outcomes, key capabilities and illustrations that have been mapped against the RCPCH Progress curriculum domains.